Comparative anatomy of respiratory bronchioles and lobular structures in mammals - Umeda, Yumi; Izawa, Takeshi; Kazama, Kei; Arai, Sachiko; Kamiie, Junichi; Nakamura, Shinichiro; Hano, Kazuki; Takasu, Masaki; Hirata, Akihiro; Rittinghausen, Susanne; Yamano, Shotaro (Journal of Toxicologic Pathology, 2025)
Rodents are widely used to study the toxicity of chemicals; however, differences between species indicate that the results from rodents are not always directly transferable to humans. The health of workers exposed to various chemicals and particulates at high doses or for long periods is at risk. Respiratory bronchioles and lobular structures, which are demarcated by interlobular septa, are key sites for occupational lung diseases such as pneumoconiosis; however, these structures vary among animal species. Understanding these differences is crucial for studying the pathology of human occupational lung diseases. However, there is a lack of reviews focusing on these structures in different species. This review explores the lung anatomy of various mammals and its functional importance in disease to connect animal studies with human occupational lung diseases. Our results indicate that artiodactyls, especially small pig breeds and goats, are ideal for research because their respiratory bronchioles and lobular structures are similar to those of humans. This review aims to enhance the use of experimental animal data and improve our understanding of human occupational lung diseases, thereby facilitating early disease detection, treatment, and prevention.